The possible negative effects of prolonged technology-based online learning during the COVID-19 pandemic on body functions and wellbeing: a review article (Journal of Medical Science, 2021)
The COVID-19 pandemic has had impact on life on a global scale, however, one of the most affected aspects are the teaching and learning practices. Advances in technology have made distance learning a good alternative option for on-site learning, as students can both interact with one another and with the tutor, use audio, video, text to learn, as well as use the internet for research purposes. However, this mode of education will extend throughout 2020 and early 2021, which could have negative implications on the health and body functions of university students. This review aims to shed light on the negative consequences of the prolonged technology-based, remote online learning on the students’ wellbeing. Therefore, in this review we will discuss some of the physiological functions and body systems which could be affected during the COVID-19 pandemic in an attempt to suggest preventive measures in advance for safe technology-based learning.